CONTENTS AND METHODOLOGY OF PREPARING FUTURE LOGISTICIANS FOR MANAGERIAL ACTIVITY - Гармаш, Т. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
In the article the concept of formation of professional readiness for managerial activity of future specialists in logistics is scientifically grounded, the methodology of formation and development of managerial competencies of future logisticians is presented. Teaching and methodological support is understood as planning, developing and creating the optimal system of educational and methodological documentation and training facilities reqired to ensure the full and qualitative process of training future logistics professionals in the aspect of forming the skills of their future professional and managerial activities. The development of educational and methodological documentation and the selection of appropriate teaching aids were carried out consistently for each stage of experimental training. Particular attention was paid to methods of activating students’ educational and cognitive activities. Based on the results of training, the students of the experimental group achieved significant positive changes relative to the levels of their readiness for managerial activity.